‘I roll my cigarette, and cycle to my club’: Playing with Stereotypes and Subverting Anti-Feminism in New Woman Writers’ Contributions to Punch - Katy Birch (Cahiers Victoriens et Edouardiens)
Punch magazine was instrumental in shaping the figure of the New Woman in the popular imagination. Critical studies of the representation of the New Woman in Punch tend to focus on its misogynistic depictions of a ‘nagging New Woman [who] can never be quiet’ (26 May 1894, 252), but alongside these satires on the New Woman were pieces by female authors, some of whom could be described as New Women themselves. This article will focus on two pieces, published in Punch just over a decade apart, by women who were committed to the cause of women’s rights: Rosaline Masson’s poem ‘The Reason Why’ (1898) and Evelyn Sharp’s short story ‘The Wreck of “The Ark”’ (1909). The authors of both of these pieces poke fun at the stereotypes surrounding the New Woman without overtly criticising Punch for its frequent ridicule of this figure. Through my discussion of these pieces I will explore these authors’ motivations for publishing in Punch, rather than a publication with a more sympathetic attitude towards women’s rights, and I will examine the trade-off that required them to mute their feminism in return for a wider audience. The article will also explore how these authors, who were both intelligent, independent women who earned money through writing, made use of humour while publishing in a periodical in which such women were generally the targets of humour rather than the originators of it. This article will highlight the role of female writers in contributing to the portrayal of women in an influential periodical and will expand the view of Punch’s representation of the New Woman beyond the familiar satires and caricatures.